2002
DOI: 10.1159/000065844
|View full text |Cite
|
Sign up to set email alerts
|

CO<sub>2</sub> Laser Surgery for Extensive, Cauliflower-Like Anogenital Condylomata acuminata: Retrospective Long-Term Study on 19 HIV-Positive and 45 HIV-Negative Men

Abstract: Background: Extensive ‘cauliflower-like’ condyloma acuminatum (CA) in males is commonly treated with CO2 laser surgery or with electrosurgery. Studies on the long-term outcome in this specific situation are scarce. Objectives: To determine the cure and recurrence rate in relation to the HIV status and endoanal location of lesions. To determine the complication rate and patient satisfaction. Methods: Questionnaire-based retrospective long-term study on 64 consecutive men (answer rate 60% or 64/107 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 13 publications
1
27
0
1
Order By: Relevance
“…There have been reports about successful treatment of HPV-associated diseases, such as common warts, verrucous carcinoma, Bowen’s disease and so on, with topical imiquimod alone, CO 2 laser surgery or a combination of topical imiquimod and CO 2 laser ablation [18, 19, 20, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…There have been reports about successful treatment of HPV-associated diseases, such as common warts, verrucous carcinoma, Bowen’s disease and so on, with topical imiquimod alone, CO 2 laser surgery or a combination of topical imiquimod and CO 2 laser ablation [18, 19, 20, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…This finding is those of similar to previous studies with far fewer HIV-infected patients. [13][14][15][16] However, there was a trend toward more complications in the HIVnoninfected patients undergoing cardiothoracic surgery; potential selection bias of the HIV-infected patients undergoing these operations cannot be excluded.…”
Section: Commentmentioning
confidence: 99%
“…19 Other sequelae include recurrent anal fissures, perianal dermatitis, and prolonged painful defecations. 20 No such complications have occurred after Harmonic® Scalpel application. Animal studies demonstrated that acute inflammation response resolved completely two weeks after Harmonic® Scalpel injury, whereas leukocyte infiltration and tissue necrosis were observed at least for four weeks after laser and bipolar electrosurgical application.…”
Section: Discussionmentioning
confidence: 99%